The influence of psychological aspects in the acceleration of degradation processes in higher educational institutions with the remote form of learning - Garmash, Sergii Volodymyrovych (Одеський національний економічний університет, 2024)
The purpose of the article is an attempt to analyze the acceleration of degradation processes in the country’s higher educational institutions with a remote form of learning in the aspect of interrelated processes that affect the development of both an individual and a society as a whole, counting students as the product of their society and their time. Special attention is paid to various psychological factors (emotional burnout of students, social isolation, anxiety due to lack of communication, lack of motivation, stress, fatigue and uncertainty, procrastination, etc.), which significantly affect the level of education in our country, which will undoubtedly affect the future development and even on the very independent existence of the country. The article proves that the remote form of learning in the current circumstances of the introduction of martial law on the territory of Ukraine is a desirable form for a short-term period. Special attention is paid to the fact that there is a dangerous trend in higher education in our country, when the concept of “the standard of higher education” is replaced by the concept of “the standardization of higher education”. The article presents the facts of the formal attitude of the majority of students to mastering scientific methods of educational work. In the assimilation of scientific information, such students are dominated by reproductive, operational memory (with the omission of essential information). Adding of knowledge to individual experience is decreasing, which is pseudo-education. The article also proves that “learning losses” already begin from a secondary school, as a result – the overall qualitative indicator of the applicant deteriorates over the years. During the work at the article, the method of expert evaluations, the method of unity of analysis and synthesis, and the method of observation, which is characterized by direct perception of phenomena and processes in their integrity and dynamics, were used. The trends highlighted in the article require further analysis in order to prevent further complication of the situation in the country’s higher education.

Метою статті є спроба проаналізувати прискорення деградаційних процесів у закладах вищої освіти країни за дистанційної форми навчання в аспекті взаємопов’язаних процесів, які впливають на розвиток як особистості, так і суспільства загалом, оскільки студенти є продуктом свого суспільства та свого часу. Особлива увага приділяється різноманітним психологічним факторам (емоційне вигорання студентів, соціальна ізоляція, тривожність через нестачу спілкування, відсутність мотивації, стрес, втома та невизначеність, прокрастинація тощо), які значною мірою впливають на рівень освіти в нашій країні, що безперечно відіб’ється на подальшому розвитку та навіть на самому незалежному існуванні країни. У статті доводиться, що дистанційна форма навчання в теперішніх обставинах запровадження військового стану на території України є бажаною формою на короткостроковий період. Особлива увага приділяється тому, що в нашій країні спостерігається небезпечний тренд у вищій школі, коли поняття «стандарт вищої освіти» підмінюється поняттям «стандартизація вищої освіти». У статті наводяться факти формального ставлення більшості студентів до оволодіння науковими методами навчальної роботи. У засвоєнні наукової інформації у таких студентів переважає репродуктивна, оперативна пам’ять (із пропуском суттєвої інформації). Знижується факт прирощування знань до індивідуального досвіду, що є псевдоосвітою. Також у статті доводиться, що «навчальні втрати» вже починаються із середньої школи, як наслідок, загальний якісний показник абітурієнта з роками погіршується. Під час роботи над статтею були використані метод експертних оцінок, метод єдності аналізу та синтезу та метод спостереження, який характеризується безпосереднім сприйняттям явищ і процесів у їхній цілісності й динаміці. Висвітлені у статті тенденції потребують подальшого аналізу задля запобігання подальшому ускладненню ситуації у вищій школі країни.
Вплив психологічних аспектів у прискоренні деградаційних процесів у вищих навчальних закладах за дистанційної форми навчання
Keywords: psychological aspects; degradation processes; remote learning; "learning losses"; emotional burnout of students; lack of motivation; stress; procrastination; interrelated processes; психологічні аспекти; деградаційні процеси; дистанційна форма навчання; "навчальні втрати"; емоційне вигорання студентів; відсутність мотивації; стрес; прокрастинація; взаємопов'язані процеси